2021
DOI: 10.1136/bmjopen-2020-042551
|View full text |Cite
|
Sign up to set email alerts
|

Nature and type of patient-reported safety incidents in primary care: cross-sectional survey of patients from Australia and England

Abstract: BackgroundPatient engagement in safety has shown positive effects in preventing or reducing adverse events and potential safety risks. Capturing and utilising patient-reported safety incident data can be used for service learning and improvement.ObjectiveThe aim of this study was to characterise the nature of patient-reported safety incidents in primary care.DesignSecondary analysis of two cross sectional studies.ParticipantsAdult patients from Australian and English primary care settings.MeasuresPatients’ sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 58 publications
2
8
0
6
Order By: Relevance
“…Despite employing a restrictive definition, this study found that 7% of the detected AEs were severe, which is similar to or higher than that reported in other studies [ 9 , 10 , 13 , 15 ], although the definitions of AEs varied among them. This estimation implies that, in every thousand consultations attended in PC, severe harm will be caused to a patient due to health care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite employing a restrictive definition, this study found that 7% of the detected AEs were severe, which is similar to or higher than that reported in other studies [ 9 , 10 , 13 , 15 ], although the definitions of AEs varied among them. This estimation implies that, in every thousand consultations attended in PC, severe harm will be caused to a patient due to health care.…”
Section: Discussionsupporting
confidence: 86%
“…The majority of studies on AEs are conducted via medical record review [ 2 ] in a hospital setting [ 3–5 ]. Several studies in a primary care (PC) setting can be found, which employed diverse methods: reporting systems [ 6–8 ] that detected incidence values of <0.1%; interviewing health professionals or patients [ 9 , 10 ], with occurrence rates of AEs between 0.05% and 5%; observational studies on consultations [ 11 ], which estimated a prevalence of AEs of 1.1%; and few studies that reviewed clinical records for the assessment of only specific types of AEs or patients at high risk [ 12–14 ], which reported rates of AEs between 0.1% and 1% [ 15–17 ]. To our knowledge, only one study in PC has investigated the global occurrence of AEs via clinical records review, including all types of AEs in the general population, although the sample was not large and the calculations were imprecise [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient involvement in reporting safety issues offers perspectives that tend to differ from the incidents reported by providers, providing a fuller picture of contributors to unsafe care. Hernan et al 29 examined such differences in patient-versus provider-reported incidents in their patient safety study in primary care settings in England and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Algunas estimaciones dicen que hasta cuatro de cada 10 pacientes sufren daños en atención primaria/ambulatoria 11 . Los errores más graves en este nivel asistencial son los relacionados con el diagnóstico, la prescripción y el uso de medicamentos 12 . Aunque los problemas acontecidos en este entorno son menos visibles que los ocurridos en el hospital, no se debe ignorar su impacto ante el gran volumen de pacientes atendidos en el primer nivel asistencial 13 .…”
Section: Objetivo Estratégico 1 (Oe 1): Conseguir Que Los Daños Evitables a Los Pacientes Sean El Estado Mental Y El Compromiso En La Plaunclassified